Outside the main entrance of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
The enclosure wall and the main entrance gateway are designed like Nagarkhana. This is the sole entrance to the Bhandasar Temple Complex, which can be reached via a flight of steps. The mulaprasada (main temple) is towering inside the enclosure wall.